2018
DOI: 10.1111/oik.05060
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore control in connected seascapes: habitat determines when population regulation occurs in the life history of a key herbivore

Abstract: Herbivore outbreaks often trigger catastrophic overgrazing events in marine macrophyte ecosystems. The sea urchin Paracentrotus lividus, the dominant herbivore of shallow Mediterranean seascapes, is capable of precipitating shifts to barrens when its populations explode.P. lividus is found ubiquitously in rocky macroalgal communities and in sandy seagrass meadows of Posidonia oceanica, two of the most important subtidal habitats in the Mediterranean. We explored if habitat-specific regulation across the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Although regional processes appear to drive broad-scale patterns of larval settlement in sea urchins, local hydrodynamics and other factors contribute to considerable fine-scale spatial variation in larval supply and settlement in sea urchins (Ebert et al 1994;Schroeter et al 1996Schroeter et al , 2009Hereu et al 2004;. For example, pelagic larval abundance and settlement of Paracentrotus lividus varies substantially in space (Hereu et al 2004;Prado et al 2012) as does post-settlement survival and abundance due to localized and habitat-dependent effects (Prado et al 2012;Boada et al 2018). Our inferences focused on temporal trends and comparison of regional-scale patterns, rather than trying to infer causes and consequences of variation in average settlement in space.…”
Section: Discussionmentioning
confidence: 99%
“…Although regional processes appear to drive broad-scale patterns of larval settlement in sea urchins, local hydrodynamics and other factors contribute to considerable fine-scale spatial variation in larval supply and settlement in sea urchins (Ebert et al 1994;Schroeter et al 1996Schroeter et al , 2009Hereu et al 2004;. For example, pelagic larval abundance and settlement of Paracentrotus lividus varies substantially in space (Hereu et al 2004;Prado et al 2012) as does post-settlement survival and abundance due to localized and habitat-dependent effects (Prado et al 2012;Boada et al 2018). Our inferences focused on temporal trends and comparison of regional-scale patterns, rather than trying to infer causes and consequences of variation in average settlement in space.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, significant mobility may occur in connected seascapes when densities of individuals are high and food resources become scarce in the original habitat. For instance, Boada et al (2018) suggested that migration of individuals from rocky macroalgal substrates into adjacent seagrass beds was responsible for the abundance and demographic structure of populations across sublittoral habitat mosaics. Since post-settlement mortality can be a considerable bottleneck in seagrass habitats (Prado et al 2009), this process can explain the presence of similar adult densities across connected seascapes (Boada et al 2018) and account for the large proportion of the plant primary production reported to be consumed by sea urchins (ca.…”
Section: Discussionmentioning
confidence: 99%
“…Factors triggering such major herbivory events have been primarily attributed to alterations in the strength of bottom-up regulation following nutrient enrichment, reduced control by top predators due to hunting or overfishing (Shepherd 1987, Estes et al 1998, Ruiz et al 2001, Tewfik et al 2007, and to changes in ocean temperature due to global warming (Vergés et al 2016). However, our ability to accurately predict herbivory impacts may also depend on a multiplicity of other variables related to foraging and feeding behavior, resource availability and accessibility (Prado & Heck 2011, Marco-Mendez et al 2012, the effect of habitat (Boada et al 2018), and the interplay between these variables.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, compounded human disturbances are compromising the persistence of Mediterranean marine forests, including overgrazing by sea urchins and non‐native species (i.e., rabbitfish), pollution and marine heatwaves (de Caralt et al, 2020 ; Sala et al, 2011 ; Verdura et al, 2021 ). Sea urchins are common on shallow rocky reefs and are the key herbivores regulating the structure of macroalgal communities and, following population outbreaks, they can trigger the shift to the barren state (Boada et al, 2018 ; Pinnegar et al, 2000 ; Sala et al, 2012 ). In particular, Paracentrotus lividus (Lamarck, 1816) and Arbacia lixula (Linneaus, 1758) are the dominant species on Mediterranean rocky reefs.…”
Section: Methodsmentioning
confidence: 99%